2015
DOI: 10.1136/archdischild-2013-305920
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation after neonatal intensive care: evidence and challenges

Abstract: Neonatologists and paediatric providers of developmental care have documented poor neurodevelopmental outcomes of infants who have received neonatal intensive care due to prematurity, perinatal neurological insults such as asphyxia or congenital anomalies such as congenital heart disease. In parallel, developmental specialists have researched treatment options in these high-risk children. The goal of this review is connect the main categories of poor outcomes (sensory and motor function, cognition, communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 40 publications
0
36
0
2
Order By: Relevance
“…Mobility programs expedite return to activities of daily living and reduce lengths of stay and cost, without affecting safety events, but they have not been adequately prospectively studied in children 10,25,26 . A single center quality initiative has shown that mobility interventions for critically ill children can be increased without negative safety effects 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility programs expedite return to activities of daily living and reduce lengths of stay and cost, without affecting safety events, but they have not been adequately prospectively studied in children 10,25,26 . A single center quality initiative has shown that mobility interventions for critically ill children can be increased without negative safety effects 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the neonatal ICU population has evidence supporting guidelines for disability risk assessment and interventions, some of which may translate to the younger PICU population 2629 . Neuromuscular junction blockade agents are associated with ICU-acquired weakness, with patients demonstrating decreased motor evoked response amplitudes on nerve conduction studies 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal tactile processing and neurological thresholds are associated with worse cognitive, motor and language outcomes in preterm infants[5,6]. Promoting optimal development and function in newborns hospitalized in NICUs may help establish the sensory building blocks of cognition, behavior and communication[33]. …”
Section: Associations Between Painful and Supportive Experiences In Tmentioning
confidence: 99%
“…Progression and influences on infant neurodevelopment (modified from Maitre review of Neurorehabilitation) . The neonatal brain at birth is immature and is influenced by prenatal, birth and postnatal events.…”
Section: Introductionmentioning
confidence: 99%